Analisis Potensi Bahaya Kerja pada Proyek Pembangunan Pintu Masuk Utama di Bandara Sultan Kaharuddin Sumbawa dengan Metode HAZOP - Mashabai, Ismi; Ruspendi, Ruspendi; Rusmalah, Rusmalah (Industrika : Jurnal Ilmiah Teknik Industri, 2024)
The construction of the main entrance to Sumbawa's Sultan Kaharuddin Airport was carried out by CV. Swadaya Mas Engineering. Based on the results of observations in the field, potential work accidents were discovered. HAZOP (Hazard and Operability Study) is a systematic, thorough, and structured hazard identification method for identifying various problems. The results of the analysis at the airport are 50% with extreme potential risk (Extreme Risk), 25% with high-risk level (High Risk), 25% with moderate risk level (Moderate Risk), and 14% with low-risk level (Low Risk) and potential classification There are 29% potential hazards in the work attitude classification. 14% potential danger in work procedure classification, and 57% potential danger in workplace classification. Suggestions for improvement (1) organize materials to make them neater by installing warning gates, (2) implement SOP and provide outreach to workers regarding the importance of K3 and the use of APD, (3) directly implement the priority of using APD. Keywords: Construction of Sumbawa Airport Entrance, CV. Swadaya Mas Engineering, HAZOP